Prevalence and risk factors associated with ectoparasite infestation of buffaloes in an Amazonian ecosystem - Helder Ribeiro Batista; Cristiane Sarturi; Felipe Nascimento Stelmachtchuk; Daniel Rocha Oliveira; Adriana Caroprezo Morini; Solange Maria Gennari; Arlei Marcili; Fernanda Aparecida Nieri Bastos; Lauro Euclides Soares Barata; Antonio Humberto Hamad Minervino (Parasites & Vectors, 2018)
Abstract Background The water buffalo (Bubalus bubalis) is well adapted in some regions of the Amazon. Of all Brazilian states, Pará contains the largest number of this species, with 510,000 animals, approximately 38% of the Brazilian buffaloes. Despite the socioeconomic importance of bubaline farming in the northern region, little is known about the prevalence of ectoparasites that affect buffalo herds. This study aimed to identify the species of buffalo ectoparasites in the municipality of Santarém, Pará, and to determine possible risk factors related to ectoparasitic infestation. A cross-sectional study was conducted by sampling 60 rural properties and 621 buffaloes for ectoparasites. When present, ectoparasites were collected for subsequent identification. Results Of all the animals sampled, 18.5% (115/621) had ectoparasites, 7.8% (49/621) had ticks from the species Rhipicephalus (Boophilus) microplus and Amblyomma cajennense (sensu stricto), and 11.5% (72/621) had lice from the Haematopinus tuberculatus species. Six animals presented mixed infestations of ticks and lice. Among the sampled farms, 51.6% (31/60) had at least one animal infested with ectoparasites. The prevalence of ticks and lice on buffaloes was associated with the farm site, with higher prevalence (11.5% ticks, 15.4% lice) in animals at dry land (OR: 16.7 and 5.7 for ticks and lice, respectively) when compared with floodplains (0.5% ticks, 3.4% lice). Buffaloes aged 1 to 12 months had more ticks whereas buffaloes aged 13 to 24 months had more lice (P < 0.05). Conclusions Buffaloes bred in the municipality of Santarém present different levels of tick and lice infestation according to the direct influence of Amazon ecosystem characteristics. The floodplain environment, widely used for buffalo farming, contributes toward minor ectoparasite infestations in these animals.